2009
DOI: 10.2176/nmc.49.146
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Stem Cells From an Adenoid Glioblastoma Multiforme

Abstract: Brain tumors may arise from and contain cancer stem cells (CSCs) capable of self-renewal, proliferation, and differentiation that recapitulate the parent tumor. These CSCs are thought to be important in gliomagenesis. Detection of CSCs invading the adjacent brain regions is important for the diagnosis and effective treatment of glioblastoma multiforme (GBM). A 57-year-old man presented with an adenoid GBM, and underwent resection of the tumor. Multipotent, self-renewing cells derived from the human adenoid GBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although many tumor cells respond to this metabolic stress through induction of the apoptotic mechanism, some cells may be able to cope with this stress through alterations in cellular metabolism (Li et al, 2004). These cells may subsequently stimulate neovascularization and contribute to further growth of the tumor (Zagzag et al, 2000;Bao et al, 2006b;Oka et al, 2009). Hypoxia also contributes to tumor growth by changing the metabolic state of the cells, resulting in the production of macromolecules needed for cellular proliferation (DeBerardinis et al, 2008).…”
Section: Growth Of Cscs In Hypoxiamentioning
confidence: 99%
“…Although many tumor cells respond to this metabolic stress through induction of the apoptotic mechanism, some cells may be able to cope with this stress through alterations in cellular metabolism (Li et al, 2004). These cells may subsequently stimulate neovascularization and contribute to further growth of the tumor (Zagzag et al, 2000;Bao et al, 2006b;Oka et al, 2009). Hypoxia also contributes to tumor growth by changing the metabolic state of the cells, resulting in the production of macromolecules needed for cellular proliferation (DeBerardinis et al, 2008).…”
Section: Growth Of Cscs In Hypoxiamentioning
confidence: 99%
“…CD133 + cell markers are positive in 60—70% of glioma tissue. Oka et al (29) reported that the percentage of tumor CSCs varied from 1.02% to 2.32% based on flow cytometric analysis. Singh et al (36) reported less than 20% of CD133 + in total tumor mass, but wide ranging variations in the CD133 + cell ratio (0.1—50% in GBM) were reported.…”
Section: The Component Amount Of Cscs In Gliomasmentioning
confidence: 99%
“…These stem cells may be the source of tumor recurrence after radiation (25). Oka et al (29) reported that CD133 + CSCs were identified in the peripheral brain regions adjacent to the tumor. They were frequently localized around vascular structures (the vascular niche).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to CD133 - cells, CD133 + cells have 32- to 56-fold more activity of MGMT. Ji et al (36) showed that CD133 + CSCs express high levels of the drug transporter gene BCRP, combined with upregulation of DNA repair protein, MGMT mRNA, and mRNAs of other genes that inhibit apoptosis including FAS-associating death domain (FADD)-like antiapoptotic molecule (FLIP), B-cell CLL/lymphoma 2 (Bcl-2), Bcl-X, and some inhibitor of apoptosis (IAP) family members (55,57,61). Nakai et al (53) showed CSCs possess stronger drug resistance to conventional anticancer drugs such as doxorubicin, etoposide (VP-16), carboplatin, and bis -chloroethylnitrosourea (BCNU) than non-stem cells of malignant gliomas.…”
Section: Introductionmentioning
confidence: 99%